Silylation of cellulose and starch - selectivity, structure analysis, and subsequent reactions - Petzold, K.; Koschella, A.; Klemm, D.; Heublein, B.
The silylation of cellulose and starch under different starting conditions is reviewed. The control of the degree of substitution (DS)and regioselectivity in dependence of the reaction pathway are discussed in detail. The synthesis of trimethylsilyl cellulose (TMSC)in the system hexamethyldisilazane (HMDS)/ammonia leads to partially and completely silylated products controlled by the amount of the components. Hydrolytic desilylation of TMSC in tetrahydrofuran (THF)/ammonia gives the partially desilylated products. The desilylation proceeds statistically along the polymer chains. The reaction of cellulose dissolved in N,N-dimethylacetamide (DMA)/LiCl with bulky thexyldimethylchlorosilane (TDSCl)in the presence of imidazole leads to 2,6-di-O-TDS cellulose. The silylation of starch dissolved in dimethylsulfoxide (DMSO)with TDSCl/pyridine results in the formation of regioselectively 2-O and 6-O functionalized silyl ethers with DS values up to 1.8. 6-O Silyl ethers of cellulose and starch were synthesized with TDSCl highly activated in the reaction system N-methylpyrrolidone (NMP)/ammonia. Twodimensional NMR techniques after subsequent modifications of the remaining OH groups have been established as important methods for the characterization of the substitution pattern of the described silyl ethers. In the case of starch, the distribution of the substituents could be detected not only in the anhydroglucose units (AGU)but also in the non-reducing end groups (NEG).
Keywords: ACETYLATION; CELLULOSE; DESILYLATION, METHYLATION; NMR ANALYSIS; REGIOSELECTIVITY; SILYLATION; STARCH; THEXYLDIMETHYLSILYL ETHER; TRIMETHYLSILYL ETHERS